Generating functional multicellular organoids from human placenta villi - Huang, Lijun; Tu, Zhaowei; Wei, Liudan; Sun, Wei; Wang, Yifan; Bi, Shilei; He, Fang; Du, Lili; Chen, Jingsi; Kzhyshkowska, Julia; Wang, Haibin; Chen, Dunjin; et al. (Advanced science, 2023)
The interaction between trophoblasts, stroma cells, and immune cells at the maternal-fetal interface constitutes the functional units of the placenta, which is crucial for successful pregnancy outcomes. However, the investigation of this intricate interplay is restricted due to the absence of efficient experimental models. To address this challenge, a robust, reliable methodology for generating placenta villi organoids (PVOs) from early, late, or diseased pregnancies using air-liquid surface culture is developed. PVOs contain cytotrophoblasts that can self-renew and differentiate directly, along with stromal elements that retain native immune cells. Analysis of scRNA sequencing and WES data reveals that PVOs faithfully recapitulate the cellular components and genetic alterations of the corresponding source tissue. Additionally, PVOs derived from patients with preeclampsia exhibit specific pathological features such as inflammation, antiangiogenic imbalance, and decreased syncytin expression. The PVO-based propagation of primary placenta villi should enable a deeper investigation of placenta development and exploration of the underlying pathogenesis and therapeutics of placenta-originated diseases.